Innovative organic nutrient management and land arrangements improve soil health and productivity of wheat (Triticum aestivum L.) in an organic farming system - Adarsh Sharma; S. K. Sharma; S. K. Sharma; Latika Vyas; Sharvan Kumar Yadav; Biswajit Pramanick; B. S. Sai Siddartha Naik; Oliver Obročník; Viliam Bárek; Marian Brestic; Ahmed Gaber; Mohammed Ali Alshehri; et al. (Frontiers in Sustainable Food Systems)
IntroductionSoil health is vital for ecosystems, but excessive use of fertilizers, chemicals, and irrigation harms soil fertility, leading to reduced yields and degradation. Thus, exploring innovative land arrangements and nutrient management for staple crops such as wheat is essential. Organic farming offers a promising solution. This study hypothesized that an appropriate land arrangement, combined with split applications of farmyard manure (FYM) and liquid organic fertilizer, can enhance wheat productivity while also improving soil health. The objective of this study was to investigate the effects of different sowing methods and organic nutrient management practices on the productivity of wheat and soil health.MethodsThis study aimed to examine the impact of sowing methods and nutrient management practices on soil health and organic wheat productivity during the winter seasons of 2021–22 and 2022–23 at the Organic Farming Unit (Agronomy), Rajasthan College of Agriculture, MPUAT, Udaipur. The experiment was arranged in a split-plot design, with three land arrangements/sowing methods in the main plot and eight nutrient management approaches in the subplots.ResultsConcerning different land arrangements, the furrow irrigated raised bed sowing (FIRB) method resulted in the maximum wheat yield (4.34 t ha−1) compared with flat row sowing and zero tillage sowing. With respect to nutrient management practices, 75% of the recommended dose of N (RDN) through the FYM was basal + 25% RDN with the 1st irrigation + Jeevamrut application at 500 L ha−1 during sowing, and the 1st irrigation + Panchagavya spraying at 5% during the booting stage resulted in the highest grain yield (4.47 t ha−1). Both the zero tillage and FIRB land arrangements resulted in better soil biological activities and microbial counts than did flat sowing. The results indicate that sowing wheat via the FIRB method, with the recommended nitrogen dose applied through split applications of FYM along with liquid organic manures such as Jeevamrut and Panchagavya, can be an excellent option for organic wheat cultivation. This approach can enhance both yield and soil health.ConclusionSeventy-five percent RDN through FYM as a basal + 25% RDN during the 1st irrigation + Jeevamrut at 500 L ha−1 during sowing and the 1st irrigation + spraying of Panchagavya at 5% during the booting stage effectively increased the growth and yield of organic wheat. With respect to land arrangements, both FIRB and zero tillage resulted in better growth, yield, and soil biological properties. The practical utility of this study is the optimization of split applications of FYM and land arrangements for organic wheat cultivation.